The politics and ethical dilemmas of architectural conservation in an unrecognised state: insights from northern Cyprus - Sabri, Reyhan; Sakalli, Belgin (Routledge Journals, Taylor & Francis Ltd, 2021)
There is little known about the architectural conservation policies, mechanisms, and dynamics within the contested boundaries of unrecognised states. This paper redresses this lack of information and discusses the situation in northern Cyprus, an exemplary case of a long-surviving de facto state. Following its secession in 1974, the Turkish Cypriot community assumed responsibility for a substantial portfolio of monuments and heritage structures with complex ethnoreligious legacies. Except for some limited local resources, conservation works have been externally-funded, mainly from Turkey, the United Nations, the United States, and the European Union. This paper explores conservation governance and the diplomatic manoeuvrings of the local and international actors . There are de facto authorities, which keep cultural heritage under their control but cannot safeguard it, and the Greek Cypriot-led Republic of Cyprus, which links the conservation of cultural heritage to resolving the Cyprus problem. As well, there are foreign agents whose growing heritage diplomacies mark their presence in northern Cyprus by providing support for conservation. The analysis reveals an imbroglio with numerous complexities and potential ethical issues and dilemmas. It suggests that heritage conservation in an unrecognised state becomes a tool of soft power for international actors and is linked to wider geo-political tensions.
Keywords: Unrecognised state; heritage diplomacy; architectural conservation patronage; ethno-religious heritage; northern cyprus